(untitled) (Diametros, 2004)
Francis Bacon’s program for modern medicine and its ethics, developed in De Dignitate et Augmentis Scientiarum (1623), includes the requirement that doctors alleviate the pain and suffering of terminally ill patients. Invoking the ancient idea of an “easy death”, Bacon calls this course of action “outward euthanasia”. This article demonstrates that, contrary to widespread opinion, Bacon does not anticipate “Dutch-style” euthanasia or “mercy-killing”, but rather palliative care without the intentional termination of a patient’s life.